Cingulate island sign on SPECT in a patient with aceruloplasminemia presenting slowly progressive dementia. Issue 6 (24th September 2020) - Umehara, Fujio; Hosoi, Yasushi; Miyajima, Hiroaki
Abstract: A 63‐year‐old Japanese woman presented with slowly progressing dementia which developed over the two years prior to admission. She had a history of diabetes mellitus since the age of 30. Laboratory findings revealed low serum copper levels and undetectable serum ceruloplasmin. MRI showed a pronounced hypointensity in the bilateral putamen, caudate, thalamus, dentate nuclei, and cerebral cortex on T2*‐weighted images. ECD‐SPECT showed hypoperfusion in bilateral parieto‐occipital lobes with cingulate island sign. We identified a homozygous nonsense mutation (TAC to TAG) at nucleotide 537 in exon 3 of the ceruloplasmin gene in the patient, resulting in the diagnosis of aceruloplasminemia.